The Effect of Imagery Exercises and Emotional Quotient on the Athletes’ Anxiety Level (Journal of Physical Education and Sports, 2019)
The athlete's level of anxiety experienced by the Glagah Wangi Demak Athletic club will cause a less than optimal appearance and have an impact on the achievements. The objective of this study is to analyze the effect of imagery exercise and emotional intelligence toward the anxiety level of Gelagah Wangi Demak Athletic Club. The method used in this study is an experimental method with 2x2 factorial designs. Techniques of analyzing the data used are Analysis of Variance (ANOVA) at significance level (α) 0.05. The populations are 25 athletes and the sample of the amount of 20 athletes, with purposive sampling through a sample based on characteristics (goals defined by the researcher). The instrument of the research is the emotional intelligence test and athlete anxiety test. The result using ANOVA analysis shows that there are differences of Fvalue = 6.568 > Ftable = 3.59 in imagery exercise. The differences emotional intelligence effect of Fvalue = 52.552) > Ftable = 3.59. There are interaction between imagery and emotional intelligence proved by Fvalue = 5.513 > Ftable = 3.59. The conclusion of the study is there are differences effects between imagery exercise (video and script). There are significant differences between athletes who have high emotional intelligence and those who have low emotional intelligence toward athlete’s anxiety level. There is an interaction between imagery exercise (video and script) and emotional intelligence toward athlete’s anxiety.